Visual exploration pattern in hemineglect. - Müri, R; Cazzoli, D; Nyffeler, T; Pflugshaupt, T (2009)
The analysis of eye movement parameters in visual neglect such as cumulative fixation duration, saccade amplitude, or the numbers of saccades has been used to probe attention deficits in neglect patients, since the pattern of exploratory eye movements has been taken as a strong index of attention distribution. The current overview of the literature of visual neglect has its emphasis on studies dealing with eye movement and exploration analysis. We present our own results in 15 neglect patients. The free exploration behavior was analyzed in these patients presenting 32 naturalistic color photographs of everyday scenes. Cumulative fixation duration, spatial distribution of fixations in the horizontal and vertical plane, the number and amplitude of exploratory saccades was analyzed and compared with the results of an age-matched control group. A main result of our study was that in neglect patients, fixation distribution of free exploration of natural scenes is not only influenced by the left-right bias in the horizontal direction but also by the vertical direction.